2007
DOI: 10.1038/ismej.2007.2
|View full text |Cite
|
Sign up to set email alerts
|

GeoChip: a comprehensive microarray for investigating biogeochemical, ecological and environmental processes

Abstract: Owing to their vast diversity and as-yet uncultivated status, detection, characterization and quantification of microorganisms in natural settings are very challenging, and linking microbial diversity to ecosystem processes and functions is even more difficult. Microarray-based genomic technology for detecting functional genes and processes has a great promise of overcoming such obstacles. Here, a novel comprehensive microarray, termed GeoChip, has been developed, containing 24 243 oligonucleotide (50 mer) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
458
0
10

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 527 publications
(474 citation statements)
references
References 42 publications
6
458
0
10
Order By: Relevance
“…Triplicate of 500 g soil were placed in plastic pots and flooded with deionized water to maintain a 2 cm layer of standing water above the soil surface. A Rhizon soil solution sampler was inserted to each pot for the collection of soil pore water at 5,10,15,20,30, and 54 days after flooding. Soil pore water was acidified to pH <2 with HCl (10 mL solution with 0.1 mL concentrated HCl) and filtered through a sterilized 0.2 μm filter before analysis of As speciation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Triplicate of 500 g soil were placed in plastic pots and flooded with deionized water to maintain a 2 cm layer of standing water above the soil surface. A Rhizon soil solution sampler was inserted to each pot for the collection of soil pore water at 5,10,15,20,30, and 54 days after flooding. Soil pore water was acidified to pH <2 with HCl (10 mL solution with 0.1 mL concentrated HCl) and filtered through a sterilized 0.2 μm filter before analysis of As speciation.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Soil redox potential (Eh) was measured at approximately 0.5 cm below the soil surface using a combined platinum and silver/silver chloride electrode system. Dissolved organic C (DOC) was measured in the pore water samples collected on day 30.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It's been demonstrated that microarray has a power equal to new generation sequencing (Claesson et al, 2009). Several types of microarrays have been used to identify the gut microorganisms, like community genome array, functional genome array and phylogenetic oligonucleotide array (Loy et Wu et al, 2004;He et al, 2007). Recently, Paliy et al developed a more sensitive microarray containing Affymetrix GeneChip platform containing 775 representative sequences of phylospecies clusters obtained from human feces and several colon sites and was able to detect bacterial DNA present at the level of 0.00025% of the total community DNA (Paliy et al, 2009).…”
Section: Microarraymentioning
confidence: 99%